Pertumbuhan & penyelenggaraan pemerintahan desa - Nurcholis, Hanif, 1959- (Ciracas, Jakarta : Erlangga, 2011)
On village government in Indonesia.
'Peraturan perundang-undangan' : p. 247.
Includes bibliographical references (p. [243]-247) and index.
Keywords: Villages -- Indonesia; Community development -- Indonesia; Community development; Rural development -- Indonesia